Correlation Between Maximum Intensity and Microvessel Density for Differentiation of Malignant From Benign Thyroid Nodules on Contrast‐Enhanced Sonography. (1st July 2014) - Jiang, Jue; Shang, Xu; Zhang, Hongli; Ma, Wenqi; Xu, Yongbo; Zhou, Qi; Gao, Ya; Yu, Shanshan; Qi, Yanhua
Abstract : Objectives: The purpose of this study was to retrospectively evaluate contrast‐enhanced sonography for differentiation of benign and malignant thyroid nodules by analyzing the correlation between maximum intensity and microvessel density. Methods: From February 2010 to May 2012, 122 patients (85 female and 37 male; mean age ± SD, 45 ± 9.1 years) with thyroid nodules (62 papillary thyroid carcinomas, 30 nodular goiters, and 30 adenomas) that underwent routine thyroid sonography and were diagnosed by surgery were included in this study. Contrast‐enhanced sonography was performed, and enhancement patterns were classified into 3 groups: high, equal, and low enhancement. As a time‐intensity curve parameter, the correlation of maximum intensity with CD31 and CD34 microvessel density counts was analyzed. Results: On contrast‐enhanced sonography, most patients with papillary thyroid carcinomas showed a heterogeneous low enhancement pattern, whereas most patients with nodular goiters showed an equal enhancement pattern, and patients with adenomas showed a high enhancement pattern. The detection of papillary thyroid carcinomas with low enhancement had sensitivity of 96.8%, specificity of 95.0%, and accuracy of 95.9%. Compared with the papillary thyroid group, the mean microvessel density counts were significantly higher in the nodular goiter and adenoma groups ( P < .05). We also found that the maximum intensity was significantly associated with CD31 and CD34 counts (CD31, r = 0.963; P < .01; CD34, r = 0.968; P < .01). Conclusions: Maximum intensity has a significant relationship with microvessel density. Contrast‐enhanced sonography is a practical and convenient means for differentiating benign from malignant thyroid nodules.